Exploring Student Achievement Gaps in School Districts Across the United States. Issue 2 (February 2020) - Hung, Man; Smith, William A.; Voss, Maren W.; Franklin, Jeremy D.; Gu, Yushan; Bounsanga, Jerry
This study examined factors contributing to achievement gaps between White and African American students in 2, 868 diverse school districts across the United States. Using pooled data across five school years (2008-2013), six grade levels (grades third to eighth, which typically include students aged 8 years-14 years) and two different subjects (math and English language), descriptive, correlational, and multiple linear regressions were used to identify relevant factors in predicting an achievement gap. Achievement gaps were largest in the south and southwest United States. In addition, results indicate that economic inequality, racial inequality, and household adult education attainment are strongly associated with Black/White student achievement gaps. School-based factors such as per pupil expenditures and teacher/student ratios were not significant predictors. Household adult education attainment was the most significant contributor to achievement gaps, with higher levels of adult education associated with larger achievement gaps, implying that high resource communities may create additional barriers for minority students.